Determinants of hedging for Malaysian corporations / Putra Faizurrahman Zahid - Zahid, Putra Faizurrahman (2015)
This study attempts to investigate the hedging determinants of non-finaneial Malaysian corporations by testing several hypotheses on how corporations decided to utilize hedging instruments (derivatives). Selective macroeconomic variables are tested as part of the macro aspect variables for systematic risks assessment. It is found that liquidity, managerial risk aversion of option compensation, blockholder shares, market value of corporation, tax preference items and the foreign exposure of firm are the significant factors for Malaysian corporations to hedge, and the only macro aspect variable is interest rate, which contributes to hedging decision. Besides investigating the determinants of hedging issue, this study also examines the financial performance of corporation’s hedging by using ROA and Tobin’s Q performance indicator, on the hedge and nonhedge corporations sub-samples. It is found that hedger and non-hedger corporations have no significant difference in terms of financial performance, except at industry or sector level. It appears that Consumer Product’s ROA, Industrial Product’s ROA and Technology’s ROA to be significantly and positively related to hedging as predicted relationship. Plantation’s Tobin’s Q and Property’s Tobin’s Q also show significant positive relationship to corporations’ hedging activities.